Municipal waste management and energy recovery in an Italian region - Cucchiella, Federica (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2012)
Diverting waste from landfill is one of the basic priorities on improving the use of resources and reducing the environmental impacts of waste management. In order to achieve this goal it is necessary to limit the amount of materials sent to final disposal and promote energy recovery. In Italy the use of recycling is registering a growing trend but the recourse to landfill is still too high with respect to European Commission targets. The aim of the paper was to analyse the financial and economic benefits that energy recovery could produce by diverting waste from landfills in an Italian region, as landfilling cannot be a solution in the long term because of its finite capacity and for various other ecological reasons. A sensitivity analysis on the critical variables of this plan and a risk analysis are also provided